23.1: Invited Paper: Colloidal Dispersion Materials for Electrophoretic Displays and Beyond. Issue 1 (June 2015) - Goulding, Mark; Smith, Nathan; Farrand, Louise; Topping, Claire; Norman, Sarah; Sauter, Annabelle; Cooper, Guy; Jin, Heui Seok; Lee, Ji Young
Abstract : Electrophoretic‐based (EP) technology is a leading option for black & white reflective display media, notably for e‐Readers. There is great future potential to extend electrophoretic and other colloidal dispersion based displays into a range of new application fields, such as digital signage, wearable displays and "smart windows". These new applications require novel particle and fluid concepts, which present many materials design challenges; especially bright colour, image stability and ultra low power consumption. The paper will discuss the state of the art and present new materials for a range of pixel architectures.